Left heart growth and biventricular repair after hybrid palliation. (6th February 2021) - Sojak, Vladimir; Bokenkamp, Regina; Kuipers, Irene; Schneider, Adriaan; Hazekamp, Mark
Abstract: : OBJECTIVES: We evaluated the outcomes of biventricular repair after initial hybrid palliation performed in small infants with various forms of left ventricle hypoplasia. METHODS: Between September 2010 and January 2020, a total of 27 patients had biventricular repair after hybrid palliation at a median age of 11 days. Indications for the hybrid approach included growth promotion of the left ventricle outflow tract and/or the aortic valve in 14 patients and that of the left ventricle in 13 patients. Seven reinterventions and 7 reoperations were performed during the interstage period. Significant growth of left ventricle parameters was noted during the median interstage period of 62 days. Sixteen subjects had aortic arch repair, ventricular septal defect closure and relief of subaortic stenosis; 5 patients had the Ross–Konno procedure; 5 patients underwent the Yasui procedure; and 1 patient had unbalanced atrioventricular septal defect and aortic arch repair. RESULTS: Twenty-three patients (85.2%) are alive at a median follow-up of 3.3 years. Two and 3 patients died early and late after achieving biventricular circulation, respectively. There were 22 reinterventions and 15 reoperations after biventricular repair. CONCLUSIONS: Hybrid palliation can stimulate left heart growth in some patients with left ventricle hypoplasia. More patients may eventually achieve biventricular circulation than was initially thought. Additional interventions and operations are foreseeable. Despite ventricular rehabilitation, some patients with borderline left ventricles may develop restrictive physiology.